2015
DOI: 10.1099/vir.0.000153
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the origin of hepatitis C virus genotype 2 in West Africa

Abstract: Hepatitis C virus (HCV) is classified into seven genotypes based on genetic diversity, and most genotypes have been found in Africa. Infections with HCV genotype 2 (HCV2) are most prevalent in West Africa and it was suggested that HCV2 originated in West Africa. To better understand the evolutionary epidemiology of HCV2 in Africa, we examined new NS5B sequences of HCV2 strains obtained from Côte d’Ivoire, Ghana and Nigeria sequenced at the Centers for Disease Control and Prevention with those available from We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The observations of long tips and lack of tight clustering in the phylogenetic tree for the Ghanaian sequences ( Fig 2 ) indicate a significant variety of HCV-2 strains circulating in a single locale in Ghana, which may be explained by either a single massive introduction of HCV strains or introduction of numerous viral lineages over a long period of time. Alternatively, this observation suggests that Ghana is, or a part of, the geographic origin of HCV-2, which is consistent with the earlier hypothesis on the origin of this genotype in West Africa [ 39 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observations of long tips and lack of tight clustering in the phylogenetic tree for the Ghanaian sequences ( Fig 2 ) indicate a significant variety of HCV-2 strains circulating in a single locale in Ghana, which may be explained by either a single massive introduction of HCV strains or introduction of numerous viral lineages over a long period of time. Alternatively, this observation suggests that Ghana is, or a part of, the geographic origin of HCV-2, which is consistent with the earlier hypothesis on the origin of this genotype in West Africa [ 39 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…When the available HCV variants sampled from West Africa were analyzed, HCV-1 and HCV-2 variants from central Africa were found to form tight clusters while the HCV variants from Ghana and other West African countries were found intermixed ( Fig 2 ). Lack of country-specific clusters and dispersion of the Ghanaian HCV variants across the entire HCV-2 in the phylogenetic tree suggest that the sample of HCV NS5B sequences in this study was obtained from a very large and heterogeneous HCV-2 population that has been circulating in Ghana [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 2 with a general frequency of 40.0% (211/528) was the main genotype found in Benin, Burkina Faso, Ghana, Guinea-Bissau and Mali (Figure 2 ). Indeed, several previous studies have reported a predominance of HCV genotype 2 in West Africa[ 75 ]. Most authors suggest a West African genotype 2 origin of HCV in the region, including The Gambia and Guinea-Bissau[ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian coalescent analysis was performed in BEAST software (v1.8.3). The GTR+I+gamma substitution model, uncorrected exponential clock model and Bayesian skygrid coalescent model were selected [ 20 ], and 5.0*10 −4 substitution/site*year was set as the prior rate [ 21 ]. The XML file was generated by BEUTi program and ran in BEAST software, with MCMC run for 300,000,000 states and sampled every 10,000 states.…”
Section: Methodsmentioning
confidence: 99%